Open Appendicectomy under Spinal Anesthesia—A Valuable Alternative during COVID-19 - Mai, Dinh Van Chi; Sagar, Alex; Claydon, Oliver; Park, Ji Young; Tapuria, Niteen; Keeler, Barrie D. (The Surgery Journal, 2021)
Introduction Concerns relating to coronavirus disease 2019 (COVID-19) and general anesthesia (GA) prompted our department to consider that open appendicectomy under spinal anesthesia (SA) avoids aerosolization from intubation and laparoscopy. While common in developing nations, it is unusual in the United Kingdom. We present the first United Kingdom case series and discuss its potential role during and after this pandemic.Methods We prospectively studied patients with appendicitis at a British district general hospital who were unsuitable for conservative management and consequently underwent open appendicectomy under SA. We also reviewed patient satisfaction after 30 days. This ran for 5 weeks from March 25th, 2020 until the surgical department reverted to the laparoscopic appendicectomy as the standard of care. Main outcomes were 30-day complication rates and patient satisfaction.Results None of the included seven patients were COVID positive. The majority (four-sevenths) had complicated appendicitis. There were no major adverse (Clavien-Dindo grade III to V) postoperative events. Two patients suffered minor postoperative complications. Two experienced intraoperative pain. Mean operative time was 44 minutes. Median length of stay and return to activity was 1 and 14 days, respectively. Although four stated preference in hindsight for GA, the majority (five-sevenths) were satisfied with the operative experience under SA.Discussion Although contraindications, risk of pain, and specific complications may be limiting, our series demonstrates open appendicectomy under SA to be safe and feasible in the United Kingdom. The technique could be a valuable contingency for COVID-suspected cases and patients with high-risk respiratory disease.
Keywords: COVID-19; SARS-CoV-2; appendicitis; appendicectomy; anesthesia; spinal